2010
DOI: 10.1164/rccm.201002-0250oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Dysfunction Is Associated with Poor Outcomes in Patients with Acute Lung Injury

Abstract: Pulmonary vascular dysfunction is common in ALI, and is independently associated with poor outcomes. Future trials targeting pulmonary vascular dysfunction may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
142
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 41 publications
8
142
0
1
Order By: Relevance
“…In ARDS, pulmonary arterial pressure has been investigated, mainly invasively, with pulmonary arterial catheterization [Squara et al 1998;Ryan et al 2014;Beiderlinden et al 2006;Osman et al 2009;Bull et al 2010], and only a few reports assessed pulmonary systolic arterial pressure with echocardiography in patients with ALI with or without ARDS [Jardin et al 1985;Boissier et al 2013;Vieillard-Baron et al 2001;Cepkova et al 2007;Mekontso-Dessap et al 2010] (Table 1). Clinical interpretation of these data is challenging, since definition of ARDS has changed over time [Murray et al 1988;Bernard et al 1994;Force et al 2012], as well as the standard of care in ARDS with the introduction of lung-protective ventilation [The Acute Respiratory Distress Syndrome Network, 2000] and conservative fluid management [Wiedemann et al 2006].…”
Section: Pulmonary Systolic Arterial Hypertensionmentioning
confidence: 99%
“…In ARDS, pulmonary arterial pressure has been investigated, mainly invasively, with pulmonary arterial catheterization [Squara et al 1998;Ryan et al 2014;Beiderlinden et al 2006;Osman et al 2009;Bull et al 2010], and only a few reports assessed pulmonary systolic arterial pressure with echocardiography in patients with ALI with or without ARDS [Jardin et al 1985;Boissier et al 2013;Vieillard-Baron et al 2001;Cepkova et al 2007;Mekontso-Dessap et al 2010] (Table 1). Clinical interpretation of these data is challenging, since definition of ARDS has changed over time [Murray et al 1988;Bernard et al 1994;Force et al 2012], as well as the standard of care in ARDS with the introduction of lung-protective ventilation [The Acute Respiratory Distress Syndrome Network, 2000] and conservative fluid management [Wiedemann et al 2006].…”
Section: Pulmonary Systolic Arterial Hypertensionmentioning
confidence: 99%
“…Fifth, hypoxic pulmonary vasoconstriction can further increase PVR. All these of mechanisms can contribute to an elevation in PVR that can occur within 48 h after the onset of ARDS, as demonstrated many years ago [3] and also more recently [4,5]. The elevation in PVR may also be exacerbated by hypercapnia and acidosis.…”
mentioning
confidence: 92%
“…Bull et al published data on 470 patients with ARDS demonstrating an increased 60-day mortality with elevated baseline transpulmonary gradient (TPG) >12 mm of Hg. Both pulmonary vascular resistance index and TPG were determined to be independent risk factors for increased 60-day mortality, number of ICU free days, ventilator free days on multivariate analysis in his study (18).…”
mentioning
confidence: 99%
“…It is difficult to objectively demonstrate pulmonary vascular dysfunction due to fact that most modern intensive care units have shied away from using pulmonary catheters. In one of the few studies that looked at pulmonary vascular dysfunction in ARDS, Bull et al (18) reported a greater than 70% incidence of pulmonary vascular dysfunction among those with acute lung injury. Right ventricular dysfunction and ACP occurs as downstream effects of pulmonary vascular dysfunction and elevation in pulmonary vascular resistance.…”
mentioning
confidence: 99%